2020
DOI: 10.1590/1982-0216/20202231320
|View full text |Cite|
|
Sign up to set email alerts
|

Educational Speech-Language Pathology in the curricula of Speech-Language Pathology Programs in Brazil

Abstract: ABSTRACT Purpose: to investigate the inclusion of Educational Speech-Language Pathology in the curricula of Speech-Language Pathology programs in Brazil. Methods: a descriptive, exploratory, documentary research based on information from public domain documents. Data were collected from the search on the website of the Conselho Federal de Fonoaudiologia, each institution’s curricula being analyzed. Results: a total of 72 higher education institutions in Brazil, offering a Speech-Language Pathology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…Along the same line of the data found in this research, a recent study 6 showed that less than half of the Brazilian undergraduate SLH programs offered specific courses on Educational SLH Pathology. Also, most of those that do offer them, the courses are only theoretical, with a course load of 40 hours or a little more than that.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Along the same line of the data found in this research, a recent study 6 showed that less than half of the Brazilian undergraduate SLH programs offered specific courses on Educational SLH Pathology. Also, most of those that do offer them, the courses are only theoretical, with a course load of 40 hours or a little more than that.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, such syllabi lack, for instance, content related to legislation, cooperation between health and education, and the educational situation in the municipality where the HEI are located. It is understood that the initial SLH training to work in educational settings must have a critical-reflexive approach and encompass the public health and education policies, besides the documents that guide the educational practices in Brazil -e.g., the Federal Constitution, Law on Guidelines and Bases (LDB, in Portuguese), National Curricular Parameters (PCNs), National Common Curricular Basis (BNCC), National Policy on Special Education in the Perspective of Inclusive Education, National Education Plan (PNE, 2014-2024), State and Municipal Plans, which must be outlined based on the PNE, and at the local level, the Pedagogical Policy Plan of the school where they will work and the training activities will be carried out 3,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, o modelo de formação que ainda hoje é vivenciado na Fonoaudiologia, os docentes repassam os modelos aprendidos na sua formação, e tais modelos são reproduzidos na atuação profissional (10) . Fica evidente, portanto, a necessidade de (re) orientar a formação dos profissionais da saúde a fim de responder às necessidades do SUS (20)(21)(22) .…”
Section: Resultsunclassified
“…Therefore, in the training format still practiced in SLH Sciences, professors reproduce the models they received in their education, which are perpetuated in professional practice (10) . This demonstrates the need to (re)direct health professional training to meet the needs at SUS (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%